Myocardial Blood Flow and Metabolic Rate of Oxygen Measurement in the Right and Left Ventricles at Rest and During Exercise Using 15O-Labeled Compounds and PET - Kudomi, Nobuyuki; Kalliokoski, Kari K.; Oikonen, Vesa J.; Han, Chunlei; Kemppainen, Jukka; Sipilä, Hannu T.; Knuuti, Juhani; Heinonen, Ilkka H. A. (Frontiers in Physiology, 2019)
Aims Simultaneous measurement of right (RV) and left ventricle (LV) myocardial blood flow (MBF), oxygen extraction fraction (OEF), and oxygen consumption (MVO2) non-invasively in humans would provide new possibilities to understand cardiac physiology and different patho-physiological states. Methods We developed and tested an optimized novel method to measure MBF, OEF, and MVO2 simultaneously both in the RV and LV free wall (FW) using positron emission tomography in healthy young men at rest and during supine bicycle exercise. Results Resting MBF was not significantly different between the three myocardial regions. Exercise increased MBF in the LVFW and septum, but MBF was lower in the RV compared to septum and LVFW during exercise. Resting OEF was similar between the three different myocardial regions ( 70%) and increased in response to exercise similarly in all regions. MVO2 increased approximately two to three times from rest to exercise in all myocardial regions, but was significantly lower in the RV during exercise as compared to septum LVFW. Conclusion MBF, OEF and MVO2 can be assessed simultaneously in the RV and LV myocardia at rest and during exercise. Although there are no major differences in the MBF and OEF between LV and RV myocardial regions in the resting myocardium, MVO2 per gram of myocardium appears to be lower the RV in the exercising healthy human heart due to lower mean blood flow. The presented method may provide valuable insights for the assessment of MBF, OEF and MVO2 in hearts in different pathophysiological states.